TRAINING OF GROUP MODEL CLINIC SUPERVISION IN DOCUMENTATION OF NURSING CARE AT SANSANI HOSPITAL, PEKANBARU - Mayenti, Fitra; Meri, Dilgu; Redho, Ahmad; Deswita, Deswita (LPPM Univ. Ibn Khaldun Bogor, 2022)
Documentation of nursing care is the responsibility of nurses in improving the quality of nursing services. Nursing documentation is an indicator of quality in assessing the quality of services provided by nurses. Good supervision can improve the competence and performance of nurses in the room. Supervision is a manager's professional support in providing assistance and direction to nursing staff to develop their abilities and competencies of nursing staff. Sansani Hospital in documenting care has made a policy that the application of nursing care documentation is according to standards, but the implementation is still not up to standard. The implementation of supervision in the documentation by the supervisor has not been optimal. Therefore, the IbM team will conduct clinical supervision training for the model group in documenting nursing care. IbM is carried out for 1 year, while the targets in this IbM are the head of the room and the team leader at Sansani Hospital. The solutions offered are socialization of clinical supervision and documentation of nursing care and simulation of the implementation of group model clinical supervision. IbM's output target is clinical supervision training on a group model in nursing care documentation developed in the form of modules and publications in online media. After the training, it was found that there was an increase in knowledge about the supervision of the model group in the documentation of nursing care.